2004
DOI: 10.1121/1.1766051
|View full text |Cite
|
Sign up to set email alerts
|

Response of multiple rigid porous layers to high levels of continuous acoustic excitation

Abstract: A model has been developed for the response of a rigid-porous hard-backed medium containing an arbitrary number of layers to high amplitude sound. Nonlinearity is introduced by means of a velocity-dependent flow resistivity in Johnson's equivalent fluid model for the complex tortuosity of each layer. Numerical solution of the resulting system of algebraic equations allows prediction of the dependence of surface impedance and reflection coefficient on the incident pressure amplitude. Measurements have been made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Typical values of Forchheimer's nonlinearity parameter n are in the range {0, 10} s/m. 2,14 For materials with n ( 1 s/m (such as mineral wool or granular material with very small particles, e.g., sand), the three effects are comparable in strength only at high level of excitation. For instance, for n ¼ 0:1 s/m acoustic pulse amplitude predicted by Eq.…”
Section: Analysis Of Dimensionless Governing Equationmentioning
confidence: 99%
“…Typical values of Forchheimer's nonlinearity parameter n are in the range {0, 10} s/m. 2,14 For materials with n ( 1 s/m (such as mineral wool or granular material with very small particles, e.g., sand), the three effects are comparable in strength only at high level of excitation. For instance, for n ¼ 0:1 s/m acoustic pulse amplitude predicted by Eq.…”
Section: Analysis Of Dimensionless Governing Equationmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] As a consequence, in the present case, we neglect Forchheimer's nonlinearity, which has been shown to play a role in some air-saturated porous media at high acoustic levels in the context of a rigid solid frame ͑equivalent fluid approximation͒. 26 A way to consider nonlinear terms in the constitutive laws has been described by Biot 44 and Donskoy et al 45 and consists in introducing a nonlinear potential H defined by…”
Section: A Nonlinear Biot Equations Inˆu S U W ‰ Formulationmentioning
confidence: 99%
“…24,22,25 Nonlinear effects have been investigated in this equivalent fluid model approximation in the case of intense sound waves. 26 For shorter wavelengths, becoming of the order of the bead diameter, scattering occurs and its modeling for such close scatterers is a hard task even if the geometry is well-known. 27 In water, owing to the lower acoustic energy dissipation than in air, several pioneering experiments have been carried out on the acoustic energy diffusion process and showed that most of the energy transports through water and that the associated waves are multiply scattered by the glass beads.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning in the United Kingdom in the 2000s, a shift in emphasis occurred from the fibrous materials previously studied to granular materials and porous metals. The theory was extended to include complex compressibility and boundary slip, 18,19 multilayer and double-porosity materials, 20,21 and time-domain solutions and pulse propagation. 22,23 Recent work on porous metals continues in China.…”
Section: Introductionmentioning
confidence: 99%